let V be Z_Module; :: thesis: for W being Submodule of V
for L being Linear_Combination of V st Carrier L c= the carrier of W holds
ex K being Linear_Combination of W st
( Carrier K = Carrier L & Sum K = Sum L )

let W be Submodule of V; :: thesis: for L being Linear_Combination of V st Carrier L c= the carrier of W holds
ex K being Linear_Combination of W st
( Carrier K = Carrier L & Sum K = Sum L )

let L be Linear_Combination of V; :: thesis: ( Carrier L c= the carrier of W implies ex K being Linear_Combination of W st
( Carrier K = Carrier L & Sum K = Sum L ) )

assume A1: Carrier L c= the carrier of W ; :: thesis: ex K being Linear_Combination of W st
( Carrier K = Carrier L & Sum K = Sum L )

then reconsider C = Carrier L as finite Subset of W ;
the carrier of W c= the carrier of V by VECTSP_4:def 2;
then reconsider K = L | the carrier of W as Function of the carrier of W, the carrier of INT.Ring by FUNCT_2:32;
A2: K is Element of Funcs ( the carrier of W, the carrier of INT.Ring) by FUNCT_2:8;
A3: dom K = the carrier of W by FUNCT_2:def 1;
now :: thesis: for w being Vector of W st not w in C holds
K . w = 0
let w be Vector of W; :: thesis: ( not w in C implies K . w = 0 )
A4: w is Vector of V by ZMODUL01:25;
assume not w in C ; :: thesis: K . w = 0
then L . w = 0 by A4;
hence K . w = 0 by ; :: thesis: verum
end;
then reconsider K = K as Linear_Combination of W by ;
take K ; :: thesis: ( Carrier K = Carrier L & Sum K = Sum L )
thus ( Carrier K = Carrier L & Sum K = Sum L ) by ; :: thesis: verum